Prehospital administration of freeze-dried plasma, is it the solution for trauma casualties?. Issue 4 (October 2017) - Shlaifer, Amir; Siman-Tov, Maya; Radomislensky, Irina; Peleg, Kobi; Shina, Avi; Baruch, Erez Nachum; Glassberg, Elon; Yitzhak, Avraham
Abstract : BACKGROUND: Hemorrhage is the leading cause of possible preventable death in the battlefield. There is an increasing evidence for the effectiveness of blood component therapy in general, and plasma infusion in particular but their use is less applicable in the prehospital setting due to logistic difficulties. Israeli Defense Force has implemented the use of freeze-dried plasma (FDP) at the point of injury (POI), this adoption of FDP use entailed doubts regarding the feasibility and effectiveness of this practice. In this article, we present our experience with the use of FDP at the POI and prehospital setting regarding the feasibility, safety, adverse reactions, and adherence to clinical practice guidelines. METHODS: This is a descriptive retrospective cohort study based on all casualties receiving FDP during January 2013 to June 2016. The study describes the injury, treatment, and outcome characteristics from POI until hospital discharge. RESULTS: During the study period, 109 casualties received FDP. The majority were men, aged 18 years to 35 years. Multiple severe injuries were found in almost half of the casualties, 78% had penetrating injury, and more than half were involved in a multicasualty event. Eighty-three percent were treated with one unit of FDP, 13% with two units, and 4% casualties with three units, nine patients (8.2%) were also treated in the prehospital setting with packed red blood cells. Fifty-seven percent fulfilled at least one criterion for the administration of FDP. Lifesaving interventions were required in 64%. In five (4.6%) cases, there were difficulties with FDP administration. Side effects were reported in one female patient. CONCLUSION: This study supports the usage feasibility of FDP at the POI and in the prehospital setting. Further adjustment of the clinical practice guidelines is required basing it not only on pathophysiologic parameters but also on clinical judgment. Further investigation of the available data is required to learn about the effectiveness of FDP at POI. Level of Evidence: Retrospective case series study, level IV.